Inhibition of LPS-Induced activation of coagulation by p38 MAPK inhibitor - Koch, Lutz; Hofer, Stefan; Weigand, Markus A.; Frommhold, David; Pöschl, Johannes; Ruef, Peter (ISRN hematology, 2012)
During Gram-negative sepsis, lipopolysaccharide (LPS) activates toll-like receptor (TLR) 4 and induces complex responses of immune system and coagulation. However, the underlying LPS signalling mechanism on coagulation activation remains complex. To determine the role of the intracellular signalling factors p38 mitogen-activated protein kinase (MAPK), nuclear factor-kappa B (NF-κB), and c-Jun N-terminal kinase (JNK) in the procoagulant response to LPS, coagulation process of human whole blood exposed to specific inhibitors was measured by thrombelastography. Samples were stimulated with LPS (100 μg/mL) after preincubation with BAY117082 (specific NF-κB inhibitor), SP600125 (specific JNK inhibitor), SB203580 (specific p38 MAPK inhibitor), or vehicle. SB203580 strongly inhibited LPS-induced coagulation activation, whereas BAY117082 and SP600125 showed no significant effect. Activation of p38 MAPK, NF-κB, and JNK and respective inhibitory effects were confirmed by Multi-Target Sandwich ELISA. In conclusion, activation of p38 MAPK is crucial for early LPS-induced activation of coagulation.
Gesehen am 05.11.2018